Sistemas orgânicos de produção para a soca da cultura da cana-de-açúcar (Saccharum spp), consorciado com milho (Zea mays), feijão (Phaseolus vulgaris) e mandioca (Manihot esculenta) - Machado, Raphael (2008)
Brazil is the major sugar cane grower, and there are two regions (Southeastern and Northeastern) with alternate harvests, which enable it keep its presence in the world market all year long. On the one hand the large sugar mills have the alcohol and sugar as their main products, on the other hand the small producers have found at the rapadura , brown sugar and the cachaça , a way to aggregate value in the market area which is little explored by large sugar mills. Right for these small growers, the organic sugar cane crops together with other basic food crops is a feasible alternative. Considering the total area cultivated with sugar cane, about 20% are from cane-growing plant, and the other 80% grown as ratoon. The general objective of this experiment was to test organic production systems for the sugar cane crops. Aiming a sustainable system for the sugar cane crops. They were tested seven different combinations of consortia with the cane ratoon, totaling eight treatments with the witness (T1: Sugar cane rattoon ; T2: Sugar cane rattoon intercropped with corn; T3: Sugar cane rattoon intercropped with beans; T4: Sugar cane rattoon intercropped with cassava; (T5)Sugar cane rattoon intercropped with corn and beans; T6: Sugar cane rattoon intercropped with corn and cassava; T7: Sugar cane rattoon intercropped with beans and cassava; T8: Sugar cane rattoon intercropped with corn, beans and cassava], which were analyzed in length, diameter, quantity, productivity and maturation of the cane treatments, in addition to the equivalent index for intermediate area of vii crops in their respective treatments. It can be concluded that the best organic production system for sugar cane crop is the one that is intercropped with corn, for it obtains good productions in both cultures.